2012
DOI: 10.1002/clc.21953
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnostic Techniques for Coronary Disease in Women

Abstract: Significant advances in medical treatment, medical technology, and the focus on sex-specific research have contributed to a reduction in cardiovascular mortality in women. Despite these advances, coronary artery disease (CAD) is the leading cause of cardiovascular death of women in the Western world. In the past 2 decades, the focused research on women at risk for CAD has helped to clarify our understanding of some of the sex-specific factors that are important in the detection of CAD. In women, the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…27 Furthermore, identifying the etiology of arrest as ischemic can be quite challenging despite advances in diagnostic tools. 28 Our finding that women compared with men are less likely to present with a shockable VT/VF rhythm has been reported in several studies. 22,29,30 Prior investigations also suggested that women have fewer arrests witnessed by bystanders, and are more likely to present with arrests at home.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…27 Furthermore, identifying the etiology of arrest as ischemic can be quite challenging despite advances in diagnostic tools. 28 Our finding that women compared with men are less likely to present with a shockable VT/VF rhythm has been reported in several studies. 22,29,30 Prior investigations also suggested that women have fewer arrests witnessed by bystanders, and are more likely to present with arrests at home.…”
Section: Discussionsupporting
confidence: 66%
“…Warning symptoms preceding cardiac arrest differ in men and women; women tend to experience more atypical symptoms, such as dyspnea, and less chest pain compared with men . Furthermore, identifying the etiology of arrest as ischemic can be quite challenging despite advances in diagnostic tools . Our finding that women compared with men are less likely to present with a shockable VT/VF rhythm has been reported in several studies .…”
Section: Discussionmentioning
confidence: 56%
“…Stress echocardiography, using exercise or dobutamine- or adenosine-mediated vasodilation, has been established as an accurate, noninvasive test for diagnosing coronary heart disease in women. 44) 45) 46) 47) The development of new, abnormal, regional wall motion during or after stress is considered an indication of myocardial ischemia. The reported sensitivity and specificity of stress echocardiography for diagnosing coronary disease ranges from 80-85%.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…ST‐segment depression (STD) induced during an exercise stress test (EST) is considered the most valuable electrocardiographic (ECG) abnormality for the diagnosis of myocardial (subendocardial) ischemia, and therefore of obstructive coronary artery disease (CAD) …”
Section: Introductionmentioning
confidence: 99%
“…ST-segment depression (STD) induced during an exercise stress test (EST) is considered the most valuable electrocardiographic (ECG) abnormality for the diagnosis of myocardial (subendocardial) ischemia, and therefore of obstructive coronary artery disease (CAD). [1][2][3] Lead aVR is usually excluded from routine analysis of ESTinduced ST-segment changes. Due to its axis orientation (+210 ), indeed, aVR is believed to not explore any specific region of the heart and have poor association with myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%